2003
DOI: 10.1126/science.1088054
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Identification of Carbonate Minerals in the Martian Dust

Abstract: Thermal infrared spectra of the martian surface indicate the presence of small concentrations (approximately 2 to 5 weight %) of carbonates, specifically dominated by magnesite (MgCO3). The carbonates are widely distributed in the martian dust, and there is no indication of a concentrated source. The presence of small concentrations of carbonate minerals in the surface dust and in martian meteorites can sequester several bars of atmospheric carbon dioxide and may have been an important sink for a thicker carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
236
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(248 citation statements)
references
References 25 publications
(53 reference statements)
12
236
0
Order By: Relevance
“…Different cations within the carbonates, typically Mg 2+ , Ca 2+ , or Fe 2+ , affect the bond lengths and vibrational frequency of the C-O bonds. The position of the emissivity peak at 6.5 µm in TES spectra of martian dust is most consistent with the presence of Mgcarbonates (Bandfield et al 2003). Although the abundance of carbonate in martian dust appears low, the ubiquity and uniformity of dust across Mars suggest that it may represent a sink as large as 1-3 bars for atmospheric CO 2 (Bandfield et al 2003) (see Sect.…”
Section: Carbonates In Martian Dustmentioning
confidence: 59%
See 1 more Smart Citation
“…Different cations within the carbonates, typically Mg 2+ , Ca 2+ , or Fe 2+ , affect the bond lengths and vibrational frequency of the C-O bonds. The position of the emissivity peak at 6.5 µm in TES spectra of martian dust is most consistent with the presence of Mgcarbonates (Bandfield et al 2003). Although the abundance of carbonate in martian dust appears low, the ubiquity and uniformity of dust across Mars suggest that it may represent a sink as large as 1-3 bars for atmospheric CO 2 (Bandfield et al 2003) (see Sect.…”
Section: Carbonates In Martian Dustmentioning
confidence: 59%
“…TIR measurements of this dust from orbit and by the two Miniature Thermal Emission Spectrometers (Mini-TES) onboard the Mars Exploration Rovers (MER) have demonstrated a common spectral character that suggests uniform mineralogy and particle size wherever the dust is observed (Christensen et al 2004;Yen et al 2005). Bandfield et al (2003) measured TIR spectra of physical mixtures of labradorite as a proxy for martian dust combined with various carbonate minerals and found that a small amount (∼2 to 5 weight %) of fine-particulate magnesite (<10 micron) provided the best fit to distinctive features above 1300 cm −1 in TES spectra of dust. Typically such a small abundance of carbonate would not be detectable, but silicates are relatively transparent at high wavenumbers where carbonates exhibit an emissivity peak near 1500 cm −1 (∼6.5 µm) that arises due to intense volume reflections at the frequency of C-O stretching vibrations.…”
Section: Carbonates In Martian Dustmentioning
confidence: 99%
“…Provided the existence of an alternative source of anions, mainly derived from volcanic volatiles [ Halevy and Head , 2014], it is expected that these ions would have bonded in evaporites (i.e., sulfates). However, in most localities on Mars, evaporites are commonly absent in clay‐dominated sediments [ Bandfield et al ., 2003; Bishop et al ., 2008; Ehlmann et al ., 2008; Osterloo et al ., 2008]. As a particular example, evaporites in Gale crater are the result of postdepositional fluid migration, in different late‐stage episodes of fluid flow; therefore, clays and evaporites at Gale have very different depositional histories, occurring spatially closely but with deposition times separated by hundreds of millions of years [ Nachon et al ., 2014; Rapin et al ., 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Carbonates are widely predicted to occur because the main constituent of Mars' atmosphere is CO 2 and this dissolves readily in water, giving a solution from which carbonate can precipitate (Equation (1)). However, apart from in minor abundances in Martian meteorites (Bridges et al 2001), and in dust (Bandfield et al 2003), carbonates have not been observed in quantity at the Martian surface. Carbonate precipitation is highly dependent on the pH of the fluid in which CO 2 is dissolved.…”
Section: The Scientific Objectives Of Watsenmentioning
confidence: 99%
“…Such secondary alteration products have been identified by thermal emission spectroscopy from orbit (Bandfield et al 2003;Bibring et al 2005). All the most recent missions to Mars have carried spectrometers capable of analysing the planet's surface at a variety of resolutions, and across a range of wavelengths, mainly from the near to mid-IR.…”
Section: Water On Mars : Evidence From Spectroscopic Analysismentioning
confidence: 99%